Changed Landscapes of Surgical Education During COVID-19 Pandemic: Implications on Future Surgeons’ Competence - Joshi, Anip (Journal of Nepal Health Research Council, 2021)
There has been a substantial impact on surgical education globally due to COVID-19 pandemic. The subtle and overt changes in surgical training programs during this pandemic along with its possible implications on the competence of future surgeons needs to be analyzed. If the essential measures are not taken in time, the surgical training programs are in a probable risk of failing to help surgery trainees successfully transition to the next phase of their surgical career. With a timely intervention for remediation, the surgery education programs will be sending surgical graduates into the community and society with the level of competency, expected from a surgeon despite COVID-19 pandemic. Keywords: COVID-19; surgical education; surgical simulation training